Análise do perfil de resistência do vírus da imunodeficiência humana tipo 1 (HIV-1) aos inibidores da transcriptase reversa não análogos de nucleosídeos (ITRNN) em Goiás - Pacheco, Priscila Ribeiro Guimarães (2010)
Objectives: To describe and analyze HIV-1 resistance mutational profiles associated with non- nucleoside reverse transcriptase inhibitors (NNRTIs) from patients experiencing antiretroviral therapy failure; at the main reference public Center in Goiás State. Methods: Samples from 474 patients were collected and processed according to the National Genotyping Network (RENAGENO), between 2006 and e 2009. Patient’s files (genotype exams) and medical records were used as data source. Number of TCD4 cells, HIV-1 viral load quantification, viral subtype and mutation profile assessment (TRUGENE HIV-1 Genotyping Test e ViroSeq System) were done according to the routine adopted by Central State Laboratory (LACEN). Resistance mutation profiles were identified using the Brazilian Algorithm and the Stanford Database Program. Cross resistance between NNRTIs: nevirapine, efavirenz and etravirine were analyzed. Descriptive and exploratory analyses were performed for socio-demographics variables and laboratory results (SPSS 15.0). Results: Samples from 126 adult patients were resistant to nevirapine (NVP) and efavirenz (EVF) Subtyping analysis showed a predominance of subtype B (86.1%), followed by BF1 recombinant (7.8%). Half of the patients received three or more antiretroviral therapy regimes. The most frequent mutations were 103N (72.2%) and 225H (22.2%). Mutations related to decreased etravirine (ETV) activity were detected in 8 codons: 98, 100, 101, 181, 188, 190 e 230 Intermediate ETV resistance were present in 27.0% and 15.1% of the samples, according to the Brazilian protocol and to Stanford Db Program, respectively. High-degree of ETV resistance were present in 10 samples (7.9%; IC95% 3.9-14.1), according to the Brazilian protocol Using the Stanford dB Program, 3 out of 126 patients (2.4%; IC95% 3.9-14.1) had high-degree of resistance. Clinical characteristics, number of T CD4 cells and viral load were not predictors to ETV resistance. Conclusions: The presence of at least one mutation potentially associated with decreased virological response to ETV was frequent, in a population highly exposed to NNRTIs. Otherwise high-degree of cross resistance to ETV was not common, suggesting that this drug could be helpful for patients failing to first generation NNRTIs.